Monte Carlo Simulation of Gamma Ray Shielding Performance of Fe55Ni28Co17 Doped PCL/ PLA Composites Using Geant4 - Kaya, Mustafa (Niyazi BULUT, 2026)
In this study, the gamma ray shielding performance of biodegradable PCL/PLA based composites reinforced with Fe55Ni28Co17 alloy was systematically investigated. The alloy was incorporated into the polymer matrix at 2%, 6%, and 10% by weight to enhance photon attenuation efficiency. Shielding behavior was evaluated over the photon energy range of 0.060–1.408 MeV using Geant4 Monte Carlo simulations and theoretical calculations performed with WinXCOM and Phy-X/PSD. Fundamental photon matter interaction parameters, including Mass attenuation coefficient (MAC), Linear attenuation coefficient (LAC), Half value layer (HVL), Tenth value layer (TVL), mean free path (MFP), atomic cross section (ACS), and electronic cross section (ECS), were determined and analyzed. The results show that increasing Fe55Ni28Co17 content significantly enhances the attenuation capability of the PCL/PLA matrix. Higher alloy loading yields increased MAC and LAC values and reduced HVL, TVL, and MFP values, indicating effective shielding with thinner material thickness. This improvement is most pronounced at low photon energies, where photoelectric absorption dominates. At intermediate energies, attenuation parameters converge due to Compton scattering, while at higher energies the influence of composition becomes limited. The close agreement between Geant4 simulations and theoretical calculations confirms the reliability of the results.
Keywords: Gamma ray shielding; MonteCarlo simulation; Biopolymer composites; Poly(ε-caprolactone) (PCL); Poly(lactic acid) (PLA).